2020
DOI: 10.1055/a-1160-5549
|View full text |Cite|
|
Sign up to set email alerts
|

Endoscopic management of gastrointestinal motility disorders – part 1: European Society of Gastrointestinal Endoscopy (ESGE) Guideline

Abstract: Main RecommendationsESGE recommends the use of a graded pneumatic dilation protocol in achalasia, starting with a 30-mm dilation and followed by a 35-mm dilation at a planned interval of 2 – 4 weeks, with a subsequent 40-mm dilation when there is insufficient relief, over both a single balloon dilation procedure or the use of a larger balloon from the outset.Strong recommendation, high quality of evidence, level of agreement 100 %.ESGE recommends being cautious in treating spastic motility disorders other than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 95 publications
0
84
0
12
Order By: Relevance
“…Botulinumtoxin A, ein Neurotoxin, das die Freisetzung von Acetylcholin an den Nervenendungen im Plexus myentericus hemmt, wirkt hier der durch [19]. Es handelt sich um eine Therapieoption für Patienten mit hoher Komorbi-dität, die ein invasiveres Verfahren nicht tolerieren [16,18].…”
Section: Injektion Von Botulinumtoxinunclassified
See 3 more Smart Citations
“…Botulinumtoxin A, ein Neurotoxin, das die Freisetzung von Acetylcholin an den Nervenendungen im Plexus myentericus hemmt, wirkt hier der durch [19]. Es handelt sich um eine Therapieoption für Patienten mit hoher Komorbi-dität, die ein invasiveres Verfahren nicht tolerieren [16,18].…”
Section: Injektion Von Botulinumtoxinunclassified
“…Auch bei der ÖGÜ-Obstruktion und denspastischenMotilitätsstörungenwird Botox eingesetzt, weist jedoch niedrige Erfolgsraten als bei der Achalasie auf, weswegen die Leitlinien einen eher zurückhaltenden Einsatz empfehlen [16,20].…”
Section: Injektion Von Botulinumtoxinunclassified
See 2 more Smart Citations
“…Inoue et al 15 introduced the concept of natural orifice transluminal endoscopic surgery (NOTES) 16 17 associated with submucosal dissection 18 and named this technique peroral endoscopic myotomy (POEM). Studies have shown that the short- to mid-term efficacy of POEM is greater than 90 % and that the procedure is associated with less postoperative pain 19 20 21 22 23 24 25 . However, this procedure is frequently associated with some common adverse effects, such as pneumoperitoneum and surgical emphysema 26 .…”
Section: Introductionmentioning
confidence: 99%